Effects of creatine supplementation on oxidative stress profile of athletes - Percário Sandro; Domingues Sérgio Paulo de Tarso; Teixeira Luiz Felipe Milano; Vieira Jose Luiz Fernandes; de Vasconcelos Flavio; Ciarrocchi Daiane Marques; Almeida Eduardo Dias; Conte Marcelo (Taylor & Francis Group, 2012)
Abstract Background Creatine (Cr) supplementation has been widely used among athletes and physically active individuals. Secondary to its performance-enhancing ability, an increase in oxidative stress may occur, thus prompting concern about its use. The purpose of this study is to investigate the effects of Cr monohydrate supplementation and resistance training on muscle strength and oxidative stress profile in healthy athletes. Methods A randomized, double-blind, placebo-controlled method was used to assess twenty-six male elite Brazilian handball players divided into 3 groups: Cr monohydrate supplemented group (GC, N = 9), placebo group (GP, N = 9), no treatment group (COT, N = 8) for 32 days. All subjects underwent a resistance training program. Blood samples were drawn on 0 and 32 days post Cr supplementation to analyze the oxidative stress markers, thiobarbituric acid reactive species (TBARS), total antioxidant status (TAS), and uric acid. Creatine phosphokinase, urea, and creatinine were also analyzed, as well. Fitness tests (1 repetition maximum - 1RM and muscle endurance) were performed on the bench press. Body weight and height, body fat percentage (by measuring skin folds) and upper muscular area were also evaluated. Statistical analysis was performed using ANOVA. Results Only GC group showed increase in 1RM (54 ± 9 vs. 63 ± 10 kg; p = 0.0356) and uric acid (4.6 ± 1.0 vs. 7.4 ± 1.6 mg/dl; p = 0.025), with a decrease in TAS (1.11 ± 0.34 vs. 0.60 ± 0.19 mmol/l; p = 0.001). No differences (pre- vs. post-training) in TBARS, creatine phosphokinase, urea, creatinine, body weight and height, body fat percentage, or upper muscular area were observed in any group. When compared to COT, GC group showed greater decrease in TAS (−0.51 ± 0.36 vs. -0.02 ± 0.50 mmol/l; p = 0.0268), higher increase in 1RM (8.30 ± 2.26 vs. 5.29 ± 2.36 kg; p = 0.0209) and uric acid (2.77 ± 1.70 vs. 1.00 ± 1.03 mg/dl; p = 0.0276). Conclusion We conclude that Cr monohydrate supplementation associated with a specific resistance program promoted a meaningful increase in muscle strength without inducing changes in body composition. The observed significant increase in uric acid and the decrease in TAS suggest that creatine supplementation, despite promoting acute effects on muscle strength improvement, might induce oxidative stress and decreases total antioxidant status of subjects.